Habitat Perkembangbiakan Spesifik Anopheles sp. di Tambang Emas Kura-Kura Banian (Perubahan Perilaku Anopheles sp.) - Liestiana Indriyati; Akhmad Rosanji; Juhairiyah Juhairiyah; Windy Tri Yuana; Erly Haryati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2016)
The results of Health Research 2010, showed that malaria was an infectious disease that the sixth cause of death cause of the sixth of death in Indonesia. Kotabaru is a malaria endemic district, especially in Puskesmas Banian, Annual Parasite Incidence 241.19 in 2014 where the cases of malaria with occurring in illegal gold mines on the slopes of Banian Mountain. It’s needed to know the factors that affect the existence of malaria in these locations. This research was observational study doing by cross-sectional study and analyzed by descriptively. Research conducted at the Gold Mine Banian Buluh Kuning village, Sungai Durian subdistric, Kotabaru district, South Kalimantan Province in February and March, 2015. The activities were catching larva and adult mosquitoes, environmental and mosquito breeding habitats observation and Mass Blood Survey. It was found Anopheles maculatus and Anopheles leucosphyrus with very low densities in area with the number of malaria cases by 22.99%. It was found divers breeding habitats of Anopheles sp on a former gold wash, former drum and former plastic containers. This indicated a behavioral change of Anopheles breeding places because previous to this the Anopheles breed in puddles on the ground or direct contact with the ground.